ABOUT THE ZEROS AND THE OSCILLATORY CHARACTER OF THE SOLUTION OF ONE AREOLAR EQUATION OF SECOND ORDER WITH ANALYTIC COEFFICIENT - Brsakoska, Slagjana (Matematichki Bilten, 2016)
In the paper, one linear areolar equation of second order with analytic coefficients is considered, regarding the zeroes and the oscillatory character of its general solution. In this equation the first derivative is missing. Some theorems will be proven and some examples will be given for different cases of the coefficient.